PANDUAN PELAKSANAAN TA MAHASISWA DKV FSD UNM - Sukarman B.; Alimuddin Alimuddin; Irfan Arifin (TANRA: Jurnal Desain Komunikasi Visual Fakultas Seni dan Desain Universitas Negeri Makassar, 2018)
Implementation of the Final Project (TA) by DKV FSD-UNM students do not have a definitive official guide. Consequently, systematic proposal, the implementation process, and systematic reports on TA produced students vary greatly due to the implementation process and the systematic writing TA students rely on experience, understanding, guidance supervisor respectively, as well as examples of proposals and reports referred to by the students. Conditions that underlies so DKV Studies Program FSD-UNM is necessary to immediately provide implementation guides TA. TA implementation guides are arranged in the form of a book that will be used in Visual Communications Design Studies Program of the Faculty of Art and Design University of Makassar. The method used in this research and development to adapt the model of development research is broadly divided into five stages, namely: (1) Phase analysis of needs, (2) The design phase, (3) stage of development, (4) Phase evaluation, and (5) Phase-setting system. Especially for the first year, research and development activities are new to the design stage. Subjects were lecturers and students TA Visual Communication Design Studies Program Faculty of Arts and Design is currently working on TA. The research data is needed at the design stage is obtained through observation and FGD, which was then analyzed quantitatively and qualitatively by type. The results obtained in this first stage in the form of a draft guidebooks TA and research instruments. TA Handbook has been designed with attention to competency courses, the characteristics of students and courses, and development principles guidebooks. The guidebooks in draft guide prepared by taking into account also the logic and system aspects, which in the later stages still need to be refined.